Síntese da Zeólita Ferrierita sem a utilização de direcionador orgânico a partir de sistema contendo sementes - Quintela, Paulo Henrique Leite (2011)
Ferrierite is a high silica zeolite, with bidimensional microporous structure, that shows remarkable performance as acid catalyst in some reactions involving hydrocarbons, especially the isomerization of n-butene to isobutene. In most cases, ferrierite synthesis requires the use of organic structure-directing agents, which increases the material production cost and, consequently, hinders its application on an industrial scale. In the present work, a synthesis route to ferrierite zeolite without using any organic structure agent was developed, starting from a reaction mixture containing seed crystals. The samples were synthesized by hydrothermal method at the temperature of 170 ºC, employing the following reagents: pseudoboehmite, sodium hydroxide, potassium hydroxide and commercial silica. Seeds were prepared from a commercial ferrierite sample with high crystallinity. The synthesis parameters evaluated were as follows: percentage of seeds (5 and 15%), water content (300 and 500 mol) and synthesis time (12 to 72 h). The samples obtained were characterized by X-ray diffraction (XRD), absorption spectroscopy in the infrared region (FT-IR), thermal analysis (TG/DTA) and scanning electron microscopy (SEM). XRD results showed that ferrierite with good crystallinity can be synthesized in a period of 12 h, using a percentage of seeds of 15%, which proves the effectiveness of the proposed methodology. The water content did not affect significantly the crystallization time of ferrierite. However, the more diluted system delayed the advent of contaminating phases such as mordenite. The samples submitted for analysis by infrared spectroscopy showed absorption bands typical of zeolitic structures. Thermal analysis results showed a mass loss of 11 to 14% in the temperature range between 30 and 500 ºC, mainly attributed to the material dehydration. Scanning electron microscopy revealed that the ferrierite produced has an irregular morphology, due to the intergrowth of crystals.